2016
DOI: 10.9790/3013-068014047
|View full text |Cite
|
Sign up to set email alerts
|

Different subgroups regarding the absence of rescue therapy in intravenous immunoglobulin-resistant Kawasaki disease

Abstract: :The objective of this study is the description of clinical outcomes regarding the absence of rescue therapy of intravenous immunoglobulin (IVIG)-resistant Kawasaki disease. I investigated the clinical outcomes of 33 IVIG-resistant patients who received the initial single IVIG therapy with the delayed use of antiinflammatory drugs (DUA). These patients were divided into two groups: 11 patients who received rescue therapies (rescue group) and 22 patients who did not receive rescue therapy (non-rescue group). On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…An initial single IVIG therapy with DUA is a challenging for preventing significant CAL caused by Kawasaki disease [3]. A recent study suggested that the decision to perform rescue therapy at 3 to 4 days after initial IVIG therapy with DUA was appropriate for preventing large CAL in initially IVIG-resistant patients [4]. However, the parameters to guide rescue therapies have not been established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial single IVIG therapy with DUA is a challenging for preventing significant CAL caused by Kawasaki disease [3]. A recent study suggested that the decision to perform rescue therapy at 3 to 4 days after initial IVIG therapy with DUA was appropriate for preventing large CAL in initially IVIG-resistant patients [4]. However, the parameters to guide rescue therapies have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…However, the parameters to guide rescue therapies have not been established. The c-reactive protein (CRP) ratio, defined as the ratio of CRP values after/before initial IVIG therapy, appeared to be useful for guiding rescue therapy [4]. However, this parameter could not identify high risk patients associated with CAL after 30 days of illness [4].…”
Section: Introductionmentioning
confidence: 99%